"EFFECTIVE ASPECTS OF USING MODERN METHODS IN TEACHING FOREIGN LANGUAGES" (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The advent of modern technology and innovative pedagogical techniques has significantly transformed the landscape of foreign language education. This paper explores the effective aspects of using modern methods in teaching foreign languages, emphasizing technology integration, communicative language teaching, task-based learning, and the flipped classroom model. Through a comprehensive review of recent literature and practical examples, the study highlights how these methods enhance student engagement, facilitate authentic language use, and improve language proficiency. The findings suggest that incorporating these modern methods can lead to more effective and dynamic language learning experiences.